Online-coupling of widely-ranged timescales to model coral reef development. (September 2021) - Hendrickx, Gijs G.; Herman, Peter M.J.; Dijkstra, Jasper T.; Storlazzi, Curt D.; Toth, Lauren T.
Abstract: The increasing pressure on Earth's ecosystems due to climate change is becoming more and more evident and the impacts of climate change are especially visible on coral reefs. Understanding how climate change interacts with the physical environment of reefs to impact coral growth and reef development is critically important to predicting the persistence of reefs into the future. In this study, a biophysical model was developed including four environmental factors in a feedback loop with the coral's biology: (1) light; (2) hydrodynamics; (3) temperature; and (4) pH. The submodels are online coupled, i.e. regularly exchanging information and feedbacks while the model runs. This ensures computational efficiency despite the widely-ranged timescales. The composed biophysical model provides a significant step forward in understanding the processes that modulate the evolution of coral reefs, as it is the first construction of a model in which the hydrodynamics are included in the feedback loop. Highlights: A biophysical model framework for coral reef evolution is developed. The model can be used to predict the coral response to the environment via process-based relations. The model bridges the gap in timescales of processes from seconds to millennia. Model predictions are within the accuracy of climate projections. The model is an efficient tool for forecasting coral reef development to inform policy makers.